Research progress on modification of hemodialysis membranes with anticoagulant properties - Xuan WANG; Zehua LI; Runjie SHI; Tiantian LI; Ruolin WANG; Chunmei NIU (Journal of Hebei University of Science and Technology)
The dialysis membrane is the most important component of hemodialyzer, and its performance depends on the feasibility and biocompatibility of removing toxic solutes. However, when the membrane material is in contact with blood directly, plasma proteins will quickly adsorb on the surface of the membrane and bind to the glycoprotein receptors on platelets, resulting in platelet activation, coagulation cascade and complement activation. This will inevitably induce coagulation and thrombosis, threatening the health and life safety of patients. In order to confer favorable anticoagulant properties upon hemodialysis membranes, it is imperative to modify the membrane materials, including surface microstructure, surface charge and wettability, thereby ensuring their controllability in terms of blood compatibility. The modification technology of the membrane was summarized. The challenges and improvement strategies faced by hemodialysis membranes in the current stage of anal dilation was elaborated. It was clarified that most of the current anticoagulant modification strategies have the problem of poor stability and easy detachment, while the modification process usually involves the usage of organic solvents and chemicals. This review also puts forward prospect on the developing direction of anticoagulant modification technology for dialysis membranes: 1) developing intelligent responsive materials to achieve dynamic anticoagulant functions; 2) constructing a biomimetic membrane surface to reduce the body's rejection reaction; 3) designing dynamic and renewable surfaces that can self-recover or regenerate; 4) carrying out green modification methods which can not only achieve efficient anticoagulant modification but also reduce environmental pollution.